First osteohistological and histotaphonomic approach of Equus occidentalis Leidy, 1865 (Mammalia, Equidae) from the late Pleistocene of Rancho La Brea (California, USA) - Tomassini, Rodrigo Leandro (2021)
Rancho La Brea (California, USA) is the most emblematic Quaternary fossiliferous locality in the world, since both the high number and diversity of the specimens recovered and their excellent preservational quality. In the last decades, paleobiological and paleoecological knowledge of the different groups of mammals from this site has increased notably; however, some aspects have not yet been inquired or there is little information. In this work we provide information on one of the most abundant mammals of this site, the equid Equus occidentalis, based on the study, from osteohistological and histotaphonomic perspectives, of thin sections of different limb bones. On the one hand, from an osteohistological viewpoint, we observe that the distribution and characterization of bone tissues in the different skeletal elements are, in general lines, similar to that mentioned for other extant and extinct equids. Cyclical growth marks allowed us to propose preliminary skeletochronological interpretations. On the other hand, from a taphonomic viewpoint, we note that all the samples reflect an excellent preservation of the bone microstructure, slightly altered by different pre- and post-burial processes. The variations recorded evidence different taphonomic history and preservation conditions among pits. This is the first study including fossil material from Rancho La Brea exclusively based on the analysis of the bone microstructure features.